STRATEGI DAKWAH PESANTREN MUKHTAR SYAFA’AT PADA MASYARAKAT - Abdul Azis; Nurhidayatullah Nurhidayatullah (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2022)
The Mukhtar Syafaat Islamic Boarding School is a boarding school that is not only concerned with educating students, but also intensely doing da'wah to the community. With their work having a positive effect on the surrounding community, they become fond of studying religious sciences. For this reason, this study focuses on highlighting how the strategies applied by the pesantren to the surrounding community. The results showed that the success of the Islamic boarding school da'wah was due to the use of cultural strategies.